Do jobs follow people or people follow jobs? A meta-analysis of Carlino–Mills studies. Issue 4 (2nd October 2017) - Hoogstra, Gerke J.; van Dijk, Jouke; Florax, Raymond J. G. M.
ABSTRACT: Do jobs follow people or people follow jobs? A meta-analysis of Carlino–Mills studies. Spatial Economic Analysis . This study examines the classic question as to whether 'jobs follow people' or 'people follow jobs' by performing a meta-analysis of 321 results from 64 Carlino–Mills studies. It is found that the results are highly divergent, but that more results point towards 'jobs following people' than towards 'people following jobs'. When it comes to the reasons for the variation in results, we find that the results are mostly shaped by the geographical location, spatial resolution, and population and employment characteristics present in the data, as well as by the model's specification, its functional form and the spatial weight matrix specification.